Strategi Pemasaran Produk Tabungan Giro IB Yang Berkonsep Mudharabah Pada Bank Sumut Syariah Capem HM. Yamin - Fitra Maulana Roza; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to find out about the marketing strategy of the iB Current Account product. This research is a type of descriptive research using a qualitative approach. Information obtained from interviews, literature review sourced from several books and critical thinking from the author. Based on the results of the author's research at PT Bank Sumut Syariah Kcp HM. Yamin. So what can be concluded from the company where the author carries out practical internship work, namely as follows; PT Bank Sumut which is one of the tools/complements of regional autonomy in the banking sector, PT Bank Sumut has a function as a driver and driver of the pace of development in the region, acting as a regional treasury holder and or carrying out regional money storage as well as a source of regional income and as a source of regional income. Commercial banks. The government considers PT Bank Sumut capable of reviving and considering the important role of PT Bank Sumut